Robot Manipulator Redundancy Resolution - Zhang, Yunong; Jin, Long (Wiley-ASME Press Series, 2017)
ntroduces a revolutionary, quadratic-programming based approach to solving long-standing problems in motion planning and control of redundant manipulators.This book describes a novel quadratic programming approach to solving redundancy resolutions problems with redundant manipulators. Known as “QP-unified motion planning and control of redundant manipulators” theory, it systematically solves difficult optimization problems of inequality-constrained motion planning and control of redundant manipulators that have plagued robotics engineers and systems designers for more than a quarter century.